MULLA SADRA AND IBN SINA ON NATURAL DISASTER - Riski Faldi (Sadra International Institute, 2025)
This article discusses the theme of natural disasters from the perspectives of Mulla Sadra and Ibn Sina, as well as their cosmological paradigms. The author hypothesizes that Islamic philosophy possesses sufficient intellectual capital to explain nature and disasters, as this school of thought harmonizes well with other sciences—such as modern science, traditional knowledge, and technology. Therefore, it is worth presenting as an alternative solution in the modern era. Islamic philosophy offers a holistic and spiritualistic perspective in understanding nature—not merely as a destructive phenomenon, but as part of the natural and human journey to accept their role as khalifah (vicegerents of God) who are responsible for fostering friendship and respect toward nature. Nature is humanity’s best companion in servitude to God and society. Nature is the manifestation of God’s presence. This study employs descriptive-analytical and phenomenological methods.